From Columns to Networks: Search toward the Elusive Single Gyroid with π‐Shaped Polyphilic Liquid Crystalline Block Molecules - Silvio Poppe; Changlong Chen; Yu Cao; Feng Liu; Carsten Tschierske (Small Science, 2025)
Polyphilic block molecules form a wide range of new liquid crystalline (LC) phases with complex morphologies on a nanometer scale. Herein the soft self‐assembly of π‐shaped p‐terphenyl‐based bolapolyphiles having two adjacent aliphatic side chains at the central benzene ring (catechol dialkyl ethers) is reported with a focus on the design of single‐network structures. Depending on the length of the side chains and temperature a series of polygonal honeycombs, a zeolite‐like LC, a lamellar phase, and two segmented network phases with cubic symmetry is found. In these networks self‐assembled glycerol spheres, forming the junctions, are interconnected by coaxial p‐terphenyl bundles. Upon side‐chain elongation, a double‐gyroid phase with three‐way junctions is replaced by the single diamond having a four‐way junction network. However, the single gyroid supposed to be formed by further side‐chain expansion could not be observed; instead, the LC self‐assembly breaks down completely. It is hypothesized that the formation of single‐network phases by bottom‐up self‐assembly in soft matter systems requires a minimum junction valence of at least 4 to stabilize the networks.